Best Practice Berbasis Komunitas Dalam Mewujudkan Ketahanan Masyarakat Terhadap Bencana - Syahrizal Koem; Rakhmat Jaya Lahay; Salmun K Nasib; Mahrifat Ismail (Universitas Lancang Kuning, 2021)
Community-based programs emphasize the community as the main actor. It started with recruitment and the establishment of community forums which became the benchmark for the success of the program. Furthermore, the community is equipped with knowledge about the identification and utilization of village potential so that the community can play practical roles in maintaining the balance of the ecosystem in the context of disaster control. The involvement of community forums in best practice is an efficient means because it provides space for forums to exchange knowledge and ideas in offering problem-solving solutions. The mining potential in Hulawa Village has a strategic role in improving the community's economy. However, it has an impact on river water resources in Hulawa Village. The direct impact observed in the field is the color change in river water due to mining activities. The potential of the village-owned by Hulawa Village can be maximized to become a village advantage. This needs to be done because it sees the opportunity for the high involvement of the Hulawa village community in village community empowerment programs.